Synthesis of biocompatible calcium phosphate matrix composite / Hazman Seli … [et al.] - Seli, Hazman; Ahmad, Zainal Arifin (2007)
The work investigates the preparation of ~-TCP composite reinforced with alumina (AhO)). The ~-TCP powder was first prepared via mixing calcium carbonate and phosphoric acid. According to XRD spectrum, the ~-TCP phases was obtained after the precursor had been calcined at 850°C for 2 hours. X-Ray diffraction (XRD) analysis, thermal gravimetric analysis (TGA) and energy dispersive X-ray (EDX) analysis of calcined powder were carried out to observe phases changes in producing the ~-TCP powder. The obtained powder was mixed with alumina at 4 different portions (l, 3, 5, 10 wt %) for 2 hours. The powder was uniaxially pressed and sintered at 3 different temperatures (950°C, 1050°C, and 1100°C). The presence of phases in the composite was determined by quantitative phase analysis (XRD).